Spiritualitas, Kecemasan, dan Stres selama Pandemi COVID-19 - Hamka Hamka; Muhammad Yusuf (Jurnal Psikologi Islam dan Budaya, 2023)
This study aims to examine the effect of spirituality on anxiety and stress during the COVID-19 pandemic. This study used quantitative method with a spiritual scale measuring instrument and the Depression, Anxiety and Stress Scale (DASS-21). There were 452 participants aged 18-55 years reside in East Kalimantan Indonesia, who were recruited through a random sampling technique. This study found that there was a significant effect of spirituality on anxiety and stress during the COVID-19 pandemic in the people of East Kalimantan Indonesia.